A client-centered relational framework on barriers to the integration of HIV and substance use services: a systematic review - Rogério Meireles Pinto; Yun Chen; Sunggeun ( Ethan) (BMC, 2019)
Abstract Background Given the close connection between human immunodeficiency virus (HIV) infection and substance use disorder (SUD), access to integrated HIV and SUD services is critical for individuals experiencing both challenges and their biopsychosocial conditions. Method Adopting an integrative method, this systematic review included 23 empirical studies published between 2000 and 2018. Articles investigated providers' and clients' perspectives on barriers to accessing integrated HIV and SUD services in various service settings (e.g., HIV primary care, SUD treatment, pharmacy). Results Using a client-centered relational framework, we identified barriers in three relational domains with "the client" as the focus of each: client-provider, client-organization, and client-system. The review shows that (1) barriers to HIV and SUD services do not exist in isolation, but in the dynamics within and across three relational domains; (2) service providers and clients often have different perceptions about what constitutes a barrier and the origin of such barriers; and (3) interprofessional and interorganizational collaborations are crucial for integrating HIV and SUD services. Conclusion This review points out the limitations of the conventional paradigm grouping barriers to service integration into isolated domains (client, provider, organization, or system). Reforms in service arrangements and provider training are recommended to address barriers to integrated services.